Preparation method for preparing pi-conjugated phosphoric acid polymer through electro-catalysis method

The electropolymerization reaction was carried out in an electrochemical workstation through an electrocatalytic polymerization method to prepare π-conjugated phosphoric acid polymer, which solved the problem of using expensive catalysts and low yields in the prior art, and achieved efficient and low-cost polymer preparation.

CN119506910APending Publication Date: 2025-02-25HEFEI XINDIAN PHOTOVOLTAIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411730110.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the preparation of π-conjugated polymers with phosphoric acid anchoring groups requires expensive nickel-based catalysts and the reaction yield is not high, which is not conducive to industrial production.

Method used

The electrocatalytic polymerization method is used to carry out the electrical polymerization reaction of three electrode configurations in an electrochemical workstation, and a platinum electrode and Ag/Ag+ electrode are used to add acetic acid and π-conjugated phosphate to the tetrabutyl tetrafluoroborate acetonitrile solution to conduct electrical polymerization, avoiding the use of high-priced catalysts and improving atomic economy and production efficiency.

Benefits of technology

The preparation of π-conjugated phosphoric acid polymers with high yield and no by-products is achieved, which reduces production costs and simplifies the post-treatment steps, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention discloses a pi-conjugated phosphoric acid polymer prepared by an electrocatalytic synthesis method and application of the pi-conjugated phosphoric acid polymer in a perovskite solar cell. And the pi-conjugated phosphate is subjected to an electropolymerization reaction. The method specifically comprises the following steps: adding a small amount of acetic acid into a tetrabutyl ammonium tetrafluoroborate acetonitrile solution, then adding pi-conjugated phosphate, and carrying out electropolymerization; and finishing the electropolymerization, taking out the working electrode, and washing the surface of the electrode to obtain the pi-conjugated phosphate polymer attached to the surface of the electrode. According to the synthesis method, the use of a high-price catalyst is avoided, the atom economy is improved, the production cost is reduced, and the post-treatment is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemical technology, and more specifically to a method for preparing a π-conjugated phosphoric acid polymer. Background Art

[0002] As global energy demand continues to rise, environmental pollution and greenhouse effect problems are becoming increasingly serious, which has prompted scientists to actively seek solutions for clean and renewable energy. As a renewable resource, solar energy has become an important field in new energy research. It has various applications, among which photoelectric conversion is one of the key technologies for efficient use of solar energy.

[0003] As early as 1883, Charles Fritts successfully manufactured the first solar cell, pioneering the conversion of sunlight into electrical energy. In the following century, scientists continued to explore and develop various types of photoelectric conversion materials, including silicon-based solar cells and compound solar cells. In 2009, Japanese scientist Miyasaka first introduced the perovskite material MAPbI3 into the field of solar cells. After nearly a decade of research and development, the efficiency of perovskite solar cells has increased from 3.8% to 25.5%. Due to its superior photoelectric performance, high light absorption rate, simple preparation process and good flexible manufacturing capabilities, perovskite solar cells have rapidly emerged as the leader of the new generation of solar cells.

[0004] In recent years, self-assembled monolayer materials (SAMs) have gradually attracted attention, especially some π-conjugated derivatives with phosphate anchoring groups (such as MeO-2PACz, 2PACz, Me-4PACz, Br-2PACz, TPA, EADR04). These materials are gradually replacing traditional hole transport layer materials due to their advantages such as simple preparation, low parasitic absorption, low material consumption and good compatibility with the substrate, and have promoted the further development of solar cell technology. This shift not only improves the performance of solar cells, but also provides new possibilities for their promotion in practical applications.

[0005] In recent decades, π-conjugated polymers have attracted increasing attention due to their excellent stability and high redox potential. Due to their high hole mobility and strong absorption in the ultraviolet spectral region, π-conjugated polymers exhibit good electro-optical activity. These characteristics make π-conjugated polymers have broad potential in multiple application fields, especially in the research and application of perovskite solar cells. In perovskite solar cells, π-conjugated polymers can be used as efficient hole transport materials to promote the effective extraction and transport of charges, thereby improving the photoelectric conversion efficiency. In addition, the excellent stability of π-conjugated polymers helps to improve the long-term reliability of devices and solve the stability problems faced by perovskite materials in practical applications. By combining π-conjugated polymers with perovskite materials, researchers can develop solar cells with better performance and longer service life. The existing method for preparing polymers with phosphate anchoring groups requires expensive nickel-based catalysts and the reaction yield is not high, which is not conducive to industrial production. Summary of the invention

[0006] In view of the problems existing in the prior art, the object of the present invention is to provide an electrocatalytic polymerization method for preparing a π-conjugated phosphoric acid polymer hole transport material.

[0007] The technical solution of the present invention is as follows Wherein: X can independently select H, halogen, amino, cyano, alkyl, alkenyl, alkynyl, aryl or heteroaryl; n can be independently selected as any integer from 0 to 100.

[0008] The electropolymerization reaction is carried out in an electrochemical workstation, using a three-electrode configuration, in which the working electrode is a platinum electrode, the auxiliary electrode is also a platinum electrode, and the reference electrode uses an Ag / Ag+ electrode. The reference electrode solution is an acetonitrile solution of silver nitrate; a small amount of acetic acid is added to the acetonitrile solution of tetrabutylammonium tetrafluoroborate, and then π-conjugated phosphate molecules are added to carry out electropolymerization; after the electropolymerization is completed, the working electrode is removed, and the electrode surface is rinsed to obtain a π-conjugated phosphate polymer attached to the electrode surface. This synthesis method avoids the use of expensive catalysts, improves atom economy, reduces production costs, and has simple post-processing.

[0009] The π-conjugated phosphate described in the step is polymerized in a tetrabutylammonium tetrafluoroborate acetonitrile solution, and the molar concentration of the π-conjugated phosphate in acetonitrile is 10-100 g / L.

[0010] In the step, the molar concentration of the acetic acid in acetonitrile is 0.2-0.3 mol / L.

[0011] In the step, the polymerization potential is 0-2V, the scanning speed is 50mV / s to 100mV / s, and a certain circle is scanned. After several times, the electropolymerization is terminated, the working electrode is taken out, and the electrode surface is rinsed with deionized water and acetonitrile respectively to obtain the polymer attached to the electrode surface.

[0012] In the steps, the number of scanning circles is 0-50 circles.

[0013] The present invention has the following advantages: 1. Compared with the existing technology, this catalytic method does not require expensive catalysts.

[0014] 2. The products accumulate on the electrode surface and are easy to separate.

[0015] 3. The reaction yield is high and there are no by-products. DETAILED DESCRIPTION

[0016] The present invention is further described below through specific implementation modes, but the protection scope of the present invention is not limited thereto.

[0017] Example 1: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode configuration, with a platinum electrode as the working electrode, a platinum electrode as the auxiliary electrode, and an Ag / Ag+ electrode (using a 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) as the reference electrode. In a 50 ml beaker, 100 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 3 g of acetic acid, and 10 g of carbazole-N-butyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was set to 0 to 2.5 V, the scan rate was 75 mV / s, and after scanning 20 circles, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode. The yield was 95%.

[0018] Example 2: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode system. The working electrode and the auxiliary electrode were both platinum electrodes, and the Ag / Ag+ electrode (using 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) was used as the reference electrode. In a 30 ml beaker, 80 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 1.5 g of acetic acid and 12 g of carbazole-N-butyl phosphate diethyl ester were added, and the reaction was carried out at room temperature. The polymerization potential was 0 to 1.8 V, and the scan rate was 60 mV / s. After 10 scans, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode surface. Yield 95% Example 3: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode configuration, with a platinum electrode as the working electrode, a platinum electrode as the auxiliary electrode, and an Ag / Ag+ electrode (using a 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) as the reference electrode. In a 25 ml beaker, 120 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 2.5 g of acetic acid, and 8 g of carbazole-N-butyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was set to 0 to 2.2 V, the scan rate was 80 mV / s, and after scanning 15 circles, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode. The yield was 95%.

[0019] Example 4: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode system. The working electrode and the auxiliary electrode were both platinum electrodes, and the Ag / Ag+ electrode (using 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) was used as the reference electrode. In a 40 ml beaker, 150 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 2 g of acetic acid and 15 g of carbazole-N-butyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was set to 0 to 2.5 V, and the scan rate was 50 mV / s. After 12 scans, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode surface. The yield was 95%.

[0020] Example 5: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode configuration, with a platinum electrode as the working electrode, a platinum electrode as the auxiliary electrode, and an Ag / Ag+ electrode (using a 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) as the reference electrode. In a 50 ml beaker, 200 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 3 g of acetic acid, and 10 g of carbazole-N-butyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was set to 0 to 2 V, the scan rate was 100 mV / s, and after scanning 25 circles, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode. The yield was 95%.

[0021] Example 6: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode configuration, with a platinum electrode as the working electrode, a platinum electrode as the auxiliary electrode, and an Ag / Ag+ electrode (using a 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) as the reference electrode. In a 50 ml beaker, 100 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 3 g of acetic acid, and 10 g of triphenylamine ethyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was set to 0 to 2.5 V, the scan rate was 75 mV / s, and after scanning 20 circles, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode. The yield was 95%.

[0022] Example 7: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode system. The working electrode and the auxiliary electrode were both platinum electrodes, and the Ag / Ag+ electrode (using 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) was used as the reference electrode. In a 30 ml beaker, 80 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 1.5 g of acetic acid and 12 g of triphenylamine ethyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was 0 to 1.8 V, and the scan rate was 60 mV / s. After 10 scans, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode surface. Yield 95% Example 8: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode configuration, with a platinum electrode as the working electrode, a platinum electrode as the auxiliary electrode, and an Ag / Ag+ electrode (using a 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) as the reference electrode. In a 25 ml beaker, 120 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 2.5 g of acetic acid, and 8 g of triphenylamine ethyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was set to 0 to 2.2 V, the scan rate was 80 mV / s, and after scanning 15 circles, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode. The yield was 95%.

[0023] Example 9: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode system. The working electrode and the auxiliary electrode were both platinum electrodes, and the Ag / Ag+ electrode (using 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) was used as the reference electrode. In a 40 ml beaker, 150 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 2 g of acetic acid and 15 g of triphenylamine ethyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was set to 0 to 2.5 V, and the scan rate was 50 mV / s. After 12 scans, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode surface. The yield was 95%.

[0024] Example 10: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode configuration, with a platinum electrode as the working electrode, a platinum electrode as the auxiliary electrode, and an Ag / Ag+ electrode (using a 0.1 mol / L silver nitrate acetonitrile solution as the reference electrode) as the reference electrode. In a 50 ml beaker, 200 ml of 0.1 mol / L tetrabutylammonium tetrafluoroborate acetonitrile solution, 3 g of acetic acid, and 10 g of triphenylamine ethyl diethyl phosphate were added, and the reaction was carried out at room temperature. The polymerization potential was set to 0 to 2 V, the scan rate was 100 mV / s, and after scanning 25 circles, the working electrode was removed, and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a polymer attached to the electrode. The yield was 95%.

[0025] The polymer hole transport material prepared in Example 1 is used as the hole transport layer to prepare a perovskite solar cell, and its structure is: glass / ITO / HTM / perovskite / C60 / BCP / Cu. Using the hole transport layer obtained in Example 1, the concentration of the ethanol solution is 2 mg mL-1, and a 1.5M MA0.7FA0.3PbI3 perovskite solution is spin-coated onto the surface of the polymer hole transport material, and thermally annealed at 100°C for 5 min. After cooling, 20nm C60 and 5nm BCP are respectively evaporated on the surface of the perovskite film. Finally, a layer of 80nm Cu is vacuum evaporated as an electrode to complete the preparation of the perovskite solar cell device. The open circuit voltage, short circuit current and filling factor of the prepared battery device are tested. Among them, the open circuit voltage Voc is 1.182V, the short circuit current density Jsc is 25.7mA / cm2, the filling factor FF is 0.85, and the photoelectric conversion efficiency is 25.6%.

[0026] The same method as in Example 1 was used, except that the raw materials were different. The specific results are as follows: Characterization of compound 1, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 4H), 1.2-5.2 (m, 8H).

[0027] Characterization of compound 2, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 6H), 1.2-5.2 (m, 8H).

[0028] Characterization of compound 3, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 6H), 1.2-5.2 (m, 14H).

[0029] Characterization of compound 4, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 4H), 1.2-5.2 (m, 9H).

[0030] Characterization of compound 5, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 2H), 1.2-5.2 (m, 9H).

[0031] Characterization of compound 6, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 2H), 1.2-5.2 (m, 15H).

[0032] Characterization of compound 7, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 12H), 1.2-5.2 (m, 4H).

[0033] Characterization of compound 8, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 12H), 1.2-5.2 (m, 4H).

[0034] Characterization of compound 9, 1H NMR (400 MHz, Chloroform-d) δ 7-9 (m, 10H), 1.2-5.2 (m, 10H).

Claims

1. A method for preparing π-conjugated phosphoric acid polymer by electrocatalysis, the reaction route is as follows: in: X can independently select H, halogen, amino, cyano, alkyl, alkenyl, alkynyl, aryl or heteroaryl; n can be independently chosen to be any integer from 0 to 100: The process includes the following steps: The electropolymerization reaction was carried out in an electrochemical workstation using a three-electrode configuration, in which the working electrode was a platinum electrode, the auxiliary electrode was also a platinum electrode, and the reference electrode used an Ag / Ag+ electrode. The solution of the reference electrode was an acetonitrile solution of silver nitrate. A small amount of acetic acid was added to the acetonitrile solution of tetrabutylammonium tetrafluoroborate, and then π-conjugated phosphate was added to carry out electropolymerization. After the electropolymerization was completed, the working electrode was removed and its surface was rinsed to obtain a π-conjugated phosphate polymer attached to the electrode. Finally, the π-conjugated phosphate polymer was dissolved in a dichloromethane solution, and trimethylsilyl bromide and methanol were added successively and stirred overnight to finally obtain a π-conjugated phosphate polymer.

2. The method for preparing a π-conjugated phosphoric acid polymer according to claim 1, characterized in that: The polymerization potential was set to 0 to 2 V, and the scanning rate was 50 mV / s to 100 mV / s. After a certain number of scans, the electropolymerization reaction was terminated, and then the working electrode was taken out and the electrode surface was rinsed with deionized water and acetonitrile, respectively, to obtain a π-conjugated phosphate polymer attached to the electrode.

3. The method for preparing a π-conjugated phosphoric acid polymer according to claim 1, characterized in that: In the tetrabutylammonium tetrafluoroborate acetonitrile solution, the molar concentration of tetrabutylammonium tetrafluoroborate is 0.01 to 0.2 mol / L.

4. The electrocatalytic method for preparing π-conjugated phosphoric acid polymer according to claim 1, characterized in that: The π-conjugated phosphoric acid polymer is selected from the following structures: